Fairness, Globalization, and Public Institutions East Asia and Beyond - Dator, Jim; Pratt, Dick; Seo, Yongseok (University of Hawai'i Press, 2006)
Who benefits from the interconnected processes often referred to as globalization? Is it a relatively few people, with most others either being harmed or at least not helped? Are the good things that globalization produces, whatever they are, widely shared? What processes lead us in one direction or another? This book examines a key dimension of globalization: its fairness. It investigates the meaning of and role fairness plays when public institutions are faced with the challenges and opportunities of globalization. Here a distinguished group of contributors, including both academics and practitioners, focuses on East and Southeast Asia, but the relevance of the issues discussed extends well beyond these regions. They present a broad-ranging examination of the intersections between fairness, globalization, and public institutions.